Determinants of c-score as a measure of financial reporting integrity in SOEs - Rizqi Zahira; Adam Zakaria; Marsellisa Nindito (Institute of Accounting Research and Novation (IARN), 2025)
Financial statements are essential decision-making tools that impact company performance and the broader economy. However, the integrity of financial statements in Indonesia particularly within State-Owned Enterprises (SOEs) continues to face challenges, as reflected in recurring cases of financial manipulation. This study examines the factors influencing the integrity of financial statements in SOEs listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, focusing on the roles of independent commissioners, intellectual capital, profitability, and audit tenure. Using panel data regression to analyze secondary data from SOEs, the results show that intellectual capital has a significant positive effect on financial reporting integrity. In contrast, profitability has a significant negative effect. However, independent commissioners and audit tenure do not show a significant influence. These findings not only contribute to the existing literature but also offer practical recommendations for companies, regulators, auditors, and investors to strengthen the management of intellectual capital in order to enhance transparency and improve the integrity of financial statements.